2010
DOI: 10.1186/1471-2180-10-131
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Virulent Bacteriophage AB1 of Acinetobacter baumannii

Abstract: BackgroundAcinetobacter baumannii is an emerging nosocomial pathogen worldwide with increasing prevalence of multi-drug and pan-drug resistance. A. baumannii exists widely in natural environment, especially in health care settings, and has been shown difficult to be eradicated. Bacteriophages are often considered alternative agent for controlling bacterial infection and contamination. In this study, we described the isolation and characterization of one virulent bacteriophage AB1 capable of specifically infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
125
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(137 citation statements)
references
References 42 publications
10
125
0
2
Order By: Relevance
“…The best temperature for phage stability was determined as 37°C, which is also reported for other bacteriophages against Enterobacter cloacae [8,18]. The TSE phages survived at all the tested temperatures from 28°C to 60°C, however the phage titer decreased when treated at 37°C to 60°C ( Figure 4 and Figure 5).…”
Section: Discussionmentioning
confidence: 97%
“…The best temperature for phage stability was determined as 37°C, which is also reported for other bacteriophages against Enterobacter cloacae [8,18]. The TSE phages survived at all the tested temperatures from 28°C to 60°C, however the phage titer decreased when treated at 37°C to 60°C ( Figure 4 and Figure 5).…”
Section: Discussionmentioning
confidence: 97%
“…It is also postulated that Ca 2+ ions may increase the concentration of phage particles at the host surface or alter the structure of a cell surface receptor so as to increase accessibility to the receptor molecules or transfer of phage nucleic acids (Russel et al, 1988;Watanabe & Takesue, 1972). Yang et al (2010) have described a burst size and duration of the latent phase that nearly correlate with our results (latent period 24 min; burst size 320 virions per cell), while Sillankorva et al (2004) found a smaller burst size and shorter duration of the latent phase. Thus, variations have been reported in the literature regarding latent time and burst size of bacteriophages.…”
Section: Discussionmentioning
confidence: 99%
“…Phage endolysins have been studied in a variety of pathogenic bacteria including A. baumannii for theirs antibacterial activity [11][12][13]. In the past three years, A. baumannii bacteriophages and endolysin have been isolated and characterized [14][15][16][17][18][19][20][21][22][23][24]. However, there are geographic differences in A. baumannii host strains.…”
Section: Introductionmentioning
confidence: 99%